2014
DOI: 10.3354/meps10928
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale climate and local weather drive interannual variability in Adélie penguin chick fledging mass

Abstract: The fledging mass of penguin chicks can be an indicator of food availability and environmental conditions at a penguin colony. For the period 1989 to 2011, we analyzed predictor variables of environmental and food resource factors acting on multiple spatial scales near Palmer Station, Antarctica, that may influence the interannual variability in Adélie penguin chick fledging mass (CFM). To understand the influence of parental Adélie penguin diet on CFM, we modeled the energy density and krill demographics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 85 publications
3
34
0
Order By: Relevance
“…Our results indicate that during the breeding season, Adélie and gentoo penguins in this area rely heavily on a single prey species that is projected to decline as a result of sea ice loss, though, the results of our tracking study show that adequate spatial separation between foraging areas may buffer against interspecific competition in a resource-limited scenario. Our results support recent research that has shown other physical mechanisms (e.g., sea ice loss and increased precipitation) and postbreeding season factors (e.g., reduced prey availability) may have a greater influence on the overall success of these two Pygoscelis species given future climate projections (Cimino, Lynch, Saba, & Oliver, 2016;Cimino et al, 2014;Fraser et al, 2013;Hinke, Salwicka, Trivelpiece, Watters, & Trivelpiece, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results indicate that during the breeding season, Adélie and gentoo penguins in this area rely heavily on a single prey species that is projected to decline as a result of sea ice loss, though, the results of our tracking study show that adequate spatial separation between foraging areas may buffer against interspecific competition in a resource-limited scenario. Our results support recent research that has shown other physical mechanisms (e.g., sea ice loss and increased precipitation) and postbreeding season factors (e.g., reduced prey availability) may have a greater influence on the overall success of these two Pygoscelis species given future climate projections (Cimino, Lynch, Saba, & Oliver, 2016;Cimino et al, 2014;Fraser et al, 2013;Hinke, Salwicka, Trivelpiece, Watters, & Trivelpiece, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Because gentoo penguins rely on krill as a primary prey resource in the Palmer area, declining krill stocks would contradict the rapid increase in gentoo penguin populations. Furthermore, a study of long‐term trends (1989–2011) of Adélie penguin chick fledgling mass (CFM) in the Palmer area determined that Adélie penguin diet characteristics had a minimal influence on CFM, suggesting that penguins had adequate prey resources during the breeding season (Cimino et al., ). Despite long‐term population trends indicating that prey resources are not currently limited in the Palmer area, we did not directly measure the distribution and density of prey within our study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the environment (here indexed by the ONI) and LKB may affect penguin performance in myriad, complex ways. For example, precipitation has been negatively correlated with both chick survival and fledgling mass 40,41 . Also, when the standing stock of krill is large, small krill are proportionally more abundant 22 , and, when small krill are more abundant, chinstrap penguins take longer foraging trips 20 .…”
Section: Resultsmentioning
confidence: 99%
“…In bird populations, the theoretical and empirical relationships between breeding phenology, resource availability and population dynamics has long been recognized (Lack, ), and with Adélie penguins these relationships have provided important insights into the probable mechanisms driving demography in the rapidly warming climate of the WAP related to changing precipitation patterns (Chapman, Hofmann, Patterson, Ribic, & Fraser, ; Cimino, Fraser, Patterson‐Fraser, Saba, & Oliver, ; Fraser & Patterson, ; Fraser et al, ; Patterson et al, ; Salihoglu, Fraser, & Hofmann, ). For example, it has been suggested that severe snowstorms and cold spring air temperature that prevent snowmelt can delay reproductive timing in Adélie penguins (Hinke, Polito, Reiss, Trivelpiece, & Trivelpiece, ; Lynch, Fagan, Naveen, Trivelpiece, & Trivelpiece, ; Lynch, Naveen, Trathan, & Fagan, ), and delayed breeding is often associated with lower breeding success (Youngflesh et al, ).…”
Section: Introductionmentioning
confidence: 99%